Components as coalgebras : the refinement dimension - Barbosa, L. S. (2006)
This paper characterizes refinement of state-based software components modeled as pointed coalgebras for some Set endofunctors. The proposed characterization is parametric on a specification of the underlying behaviour model introduced as astrong monad. This provides a basis to reason about (and transform) state-based software designs. In particular it is shown how refinement can be applied to the development of the inequational subset of a calculus of generic software components.